South Asia Economic Focus, Spring 2021 : South Asia Vaccinates - World Bank (Washington, DC: World Bank, 2021)
South Asia region’s economies are beginning to recover, though unevenly: economic activity in industry and export sectors have recovered to pre-COVID levels but some labor-intensive services sectors and tourism have not. Inequality has worsened on many dimensions. The process of vaccinating South Asia’s population is underway, with India taking a leading role in production. The socioeconomic benefits of vaccinating most South Asians as soon as possible outweighs the cost by multiple times, and thus justifies having public sector financing. Cracks in the primary health care system became evident since the pandemic began, and the vaccine rollout is likely to have other additional challenges such as delays in production, bottlenecks in supply chain logistics and vaccine hesitancy from some groups (which could delay the process of herd immunity). There are also tradeoffs in the priorities that should be established in deciding who gets the vaccine first.